2014
DOI: 10.3141/2417-05
|View full text |Cite
|
Sign up to set email alerts
|

Value of Crowding on Public Transport in île-de-France, France

Abstract: This paper describes the results of a research project that aimed to establish passenger values of crowding on public transport services in the Paris region. Qualitative research, stated preference (SP) experiments, and passenger counts and surveys were conducted to obtain such values. A simple method was developed to quantify the passenger benefits of specific public transport projects aiming to reduce crowding on existing lines. This method was applied in a case study to the regional rail (RER) RER Line E ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 4 publications
5
59
0
1
Order By: Relevance
“…Recent contributions like Kroes et al (2014) and Hörcher et al (2017) show that the cost of crowding can be captured in a revealed preference framework as well, especially when demand patterns can be recovered using smart card and vehicle location data. In terms of the magnitude of disutilities, these empirical results reveal that the cost of crowding may be similar to the cost of uncrowded travel time.…”
Section: Congestion In Microeconomicsmentioning
confidence: 99%
“…Recent contributions like Kroes et al (2014) and Hörcher et al (2017) show that the cost of crowding can be captured in a revealed preference framework as well, especially when demand patterns can be recovered using smart card and vehicle location data. In terms of the magnitude of disutilities, these empirical results reveal that the cost of crowding may be similar to the cost of uncrowded travel time.…”
Section: Congestion In Microeconomicsmentioning
confidence: 99%
“…Incorporating convenience can clearly alter the outcome of costbenefit assessments of projects and policies. For example, the Paris experience (Kroes et al, 2013) demonstrates that counting the benefits of reducing crowding added around 6% to the total benefits of the investment to extend RER line E 13 .…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Our view is that this is not supported by the evidence. Kroes et al (2013) concluded in their study of crowding penalties in Paris:…”
Section: Conclusion On Crowding Multipliersmentioning
confidence: 99%
See 2 more Smart Citations